MANAJEMEN MODERNISASI PENDIDIKAN ISLAM BERWAWASAN LINGKUNGAN DI PONDOK PESANTREN NURUL HARAMAIN NARMADA LOMBOK BARAT: MANAJEMEN MODERNISASI PENDIDIKAN ISLAM BERWAWASAN LINGKUNGAN DI PONDOK PESANTREN NURUL HARAMAIN NARMADA LOMBOK BARAT - zuhaeriah zuhaeriah (Schemata: Jurnal Pasca Sarjana IAIN Mataram, 2019)
The current situation is a modern era that cannot be released. Thus it certainly becomes a challenge for the current Islamic education system in developing its institution. Therefore, concrete efforts are needed in contextualizing conditions that are in accordance with the guidance of his time. Thus the management of Islamic education modernization with an environmental perspective of thinking with a pattern that refers to social change. This study is a field research with a qualitative approach in which the researcher tries to describe the research subject. Data collection methods, researchers used the method of observation, interviews / interviews and documentation. As for the analysis, researchers used a qualitative analysis of interactive models. The results of this study Management of Modernization of Islamic Education with Environmental Insight in Nurul Haramain Narmada Islamic Boarding School in West Lombok is through four aspects including: (1) Pesantren based on IT / Multimedia in the Literacy Aspect of Environment, (2) Waste Management with Appropriate Technology Approach, (3) ) Modernization of Education with Environmental Sanitation Aspects (4) Hidden Curriculum Approach for Personal Religious Studies. While the efforts made in implementing the Modernization of Islamic Education Management with Environmental Insights namely; (1) environmental care approach / eco-pesantren program (2) Haramain green management perspective (3) Improving environmental conservation management models (4) Applying volunteer spirit (Philanthropy). This study also concludes that the management of modernization of Islamic education with an environmental perspective on Islamic education is a framework for thinking with the model of locality development or the development of local communities from aspects of local wisdom. Such values are the principle of an approach in creating public awareness to preserve the environment and models in the approach to protecting the environment.